2019
DOI: 10.1016/j.ebiom.2019.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose-escalation study to determine the safety, tolerability, preliminary efficacy and pharmacokinetics of an intratumoral injection of tigilanol tiglate (EBC-46)

Abstract: Background: Tigilanol tiglate, a short-chain diterpene ester, is being developed as intratumoral treatment of a broad range of cancers. We conducted the first-inhuman study of intratumoral tigilanol tiglate in patients with solid tumors. Methods: Tigilanol tiglate was administered in a multicentre, non randomized, single-arm study, with escalating doses beginning with 0¢06 mg/m 2 in tumors estimated to be at least twice the volume of injection (dose-escalation cohorts). Patients with smaller tumors were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 18 publications
2
47
0
2
Order By: Relevance
“…In respect to dose rate, it is interesting that despite the 30% lower tigilanol tiglate dose per unit of tumor volume, the progression and timing of critical clinical events associated with the mode of action of tigilanol tiglate in tumor destruction and subsequent wound resolution (viz. induction of the acute inflammatory response, haemorrhagic necrosis of the tumor, and tumor slough) in these equine cases was very similar to that reported previously in treatment of canine and human tumors (1,4). This is consistent with horses having a higher sensitivity to inflammatory challenges and apparently lower thresholds, compared to canines and humans, for activation of key pro-inflammatory mediators (such as IL-1β and TNF-α) that are induced by tigilanol tiglate and which are involved in early stage initiation and amplification of acute phase responses (10,11).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In respect to dose rate, it is interesting that despite the 30% lower tigilanol tiglate dose per unit of tumor volume, the progression and timing of critical clinical events associated with the mode of action of tigilanol tiglate in tumor destruction and subsequent wound resolution (viz. induction of the acute inflammatory response, haemorrhagic necrosis of the tumor, and tumor slough) in these equine cases was very similar to that reported previously in treatment of canine and human tumors (1,4). This is consistent with horses having a higher sensitivity to inflammatory challenges and apparently lower thresholds, compared to canines and humans, for activation of key pro-inflammatory mediators (such as IL-1β and TNF-α) that are induced by tigilanol tiglate and which are involved in early stage initiation and amplification of acute phase responses (10,11).…”
Section: Discussionsupporting
confidence: 87%
“…Following treatment with tigilanol tiglate, the tumors in both equine patients followed a pattern of clinical response consistent with that seen and reported with the drug in other species and tumor types including canine mast cell tumors ( 1 , 3 ), a variety of human neoplasias ( 4 ), and murine tumors ( 2 , 5 ). This clinical response is directly related to the mode of action of tigilanol tiglate in tumor destruction and involves localized bruising and inflammation/oedema developing at the treatment site within the first 24 h, followed by haemorrhagic necrosis of the tumor mass and finally slough of the necrotic tumor leaving a treatment site wound which usually heals uneventfully via secondary intention without the need for bandaging or other interventions ( 1 ).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…A great deal of studies show that intratumoral injection of drugs has been proven to have a positive effect after many years of clinical research, can provide high drug concentrations at the tumor site with minimal exposure of nontarget tissues, and can prolong patient survival and improve quality of life [24][25][26]. Since Sugiura [27] first reported that Evidence-Based Complementary and Alternative Medicine PEI (percutaneous alcohol injection therapy) was adopted to treat liver cancer in 1983, the related research and clinical applications in the field have attracted wide attention.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an epoxy-tigliane diterpene, tigilanol tiglate (formerly EBC46), from the Queensland tropical endemic species Fontainea picrosperma C. T. White, has been discovered and shown to have significant anticancer activity [ 7 ]. Tigilanol tiglate has been approved by the European Medicines Authority [ 8 ] as a novel canine therapy for mast cell tumours [ 9 ] and is currently in clinical trials to assess its potential as a human anticancer therapeutic [ 10 ].…”
Section: Introductionmentioning
confidence: 99%